British radio drama and the avant-garde in the 1950s. Issue 4 (2nd October 2017) - Chignell, Hugh
Abstract : The BBC in the 1950s was a conservative and cautious institution. British theatre was at the same time largely commercial and offered a glamourous distraction from wider social and political realities. During the decade, however, new avant-garde approaches to drama emerged, both on the stage and on radio. The avant-garde was particularly vibrant in Paris, where Samuel Beckett was beginning to challenge theatrical orthodoxies. Initially, managers and producers in BBC radio rejected a radio version of Beckett's, Waiting for Godot and other experimental work was viewed with distaste but eventually Beckett was accepted and commissioned to write All That Fall (1957), a masterpiece of radio drama. Other Beckett broadcasts followed, including more writing for radio, extracts from his novels and radio versions of his stage plays as well as plays by the experimental radio dramatist, Giles Cooper. This article examines the different change agents which enabled an initially reluctant BBC to convert enthusiastically to the avant-garde. A networked group of younger producers, men and women, played a vital role in the acceptance of Beckett as did the striking pragmatism of senior radio managers. A willingness to accept the transnational cultural flow from Paris to London was also an important factor. The attempt to reinvent radio drama using 'radiophonic' sound effects (pioneered in Paris) was another factor for change and this was encouraged by growing competition from television drama on the BBC and ITV. The acceptance and eventual championing of avant-garde drama in the late 1950s reveal how the BBC's commitment to public service broadcasting facilitated a flowering of experimental and avant-garde drama during radio drama's golden age.